Putusan Mahkamah Konstitusi Nomor 13/PUU-XV/2017 Tentang Uji Materil Pasal 153 Ayat (1) Huruf F Undang-Undang Nomor 13 Tahun 2003 Ditinjau Dari Aspek Keadilan - Faqih Afif Ridlo; Abdul Qodir (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractThis study aims to find out the legal basis for the Constitutional Court's consideration in granting material judgments in Article 153 Paragraph (1) letter f of Law Number 13 Year 2003 concerning Labor that is considered to be contradictory to the 1945 Constitution Article 28B Paragraph (1) and Article 28D Paragraph (2) . In addition to knowing aspects of justice and benefits to the legal considerations of the Constitutional Court which grants the material test Article 153 Paragraph (1) letter f of Law Number 13 Year 2003 concerning Labor. This research method uses a normative juridical legal research approach, while the type of research used is qualitative analytical descriptive, and data collection techniques are library research. From this research it is known that the granting of the marriage of workers in one company is to safeguard the basic rights of workers, namely the right to work and also the right of family and continuing offspring, as stated in Article 28B Paragraph (1) and Article 28D Paragraph (2) of the 1945 Constitution. This is a form of fulfillment of the state of basic rights that must be possessed by all Indonesian people as a whole without exception as a form of justice.Keywords: Decision, Constitutional Court, Justice Aspects